2015
DOI: 10.1080/14789949.2015.1037331
|View full text |Cite
|
Sign up to set email alerts
|

Implicit attitudes toward violence and their relation to psychopathy, aggression, and socially adaptive behaviors in forensic psychiatric inpatients

Abstract: In order to investigate the relation between implicit attitudes toward violence and different aspects of violent and social behavior in Dutch forensic psychiatric inpatients, an implicit association test was related to measures of psychopathy, aggression, and socially adaptive behaviors. Results indicated that all patients had negative implicit attitudes toward violence. Although implicit attitudes toward violence were unrelated to several self-report measures of aggression, there was a significant positive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 62 publications
1
13
1
Order By: Relevance
“…Also, after an anger induction an automatic self-aggression association was shown in antisocial patients (Lobbestael et al, 2009). Furthermore, Zwets et al (2015) showed that a more positive association with violence was associated with the antisocial facet of psychopathy and self-reported hostility, while a more negative association with violence was related to more socially adapted behavior. Following these studies, automatic associations with aggression may be predictive of violent incidents in forensic psychiatric inpatients.…”
Section: Introductionmentioning
confidence: 90%
“…Also, after an anger induction an automatic self-aggression association was shown in antisocial patients (Lobbestael et al, 2009). Furthermore, Zwets et al (2015) showed that a more positive association with violence was associated with the antisocial facet of psychopathy and self-reported hostility, while a more negative association with violence was related to more socially adapted behavior. Following these studies, automatic associations with aggression may be predictive of violent incidents in forensic psychiatric inpatients.…”
Section: Introductionmentioning
confidence: 90%
“…Also, such measures are believed to be less dependent on the capacity for introspection (Greenwald, McGhee, & Schwartz, 1998;Roefs et al, 2011). Previous research using indirect assessment has proven useful in determining the external correlates of psychopathy, by showing, for example, that psychopathy is associated with relatively positive indirect attitudes towards aggression and violence (Snowden, Gray, Smith, Morris, & MacCulloch, 2004;Zwets et al, 2015). These attitudes are not necessarily related to psychopathy when assessed in a more explicit way (Snowden et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers typically measure violent cognition by having offenders complete self-report questionnaires (such as the Velicer Attitudes Toward Violence Scale; Velicer et al, 1989) about criminal attitudes and beliefs. Although there is empirical evidence that self-report data can have predictive validity (Mills, Loza, & Kroner, 2003), some authors suggest that respondents’ ability for introspection (Nunes, Firestone, & Baldwin, 2007) and social desirability compromise the use of self-report instruments (Zwets et al, 2015), especially in the case of some mental disorders (Roefs et al, 2011).…”
mentioning
confidence: 99%